2013
DOI: 10.1029/2012jd018382
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change, ozone recovery, and increasing methane on surface ozone and the tropospheric oxidizing capacity

Abstract: [1] Using a stratosphere-troposphere chemistry-climate model, we compare the impacts of climate change, stratospheric ozone recovery, and methane increases on surface ozone and the tropospheric oxidizing capacity by 2050. Methane increases lead to a decreasing OH, particularly in the northern subtropics during summer. Stratospheric ozone recovery causes small increases of surface OH driven by increased stratosphere-troposphere exchange, occurring during parts of the year in the southern extratropics. Troposphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
73
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 55 publications
3
73
2
Order By: Relevance
“…Stevenson et al, 2006;Zeng et al, 2008;Kawase et al, 2011;Morgenstern et al, 2013;Young et al, 2013). For the ozone burden, Kawase et al (2011) also find increases under RCP4.5 and 8.5 in sensitivity tests that are similar to the CC4.5 and CC8.5 runs of this study.…”
Section: Ozone Burdensupporting
confidence: 55%
See 1 more Smart Citation
“…Stevenson et al, 2006;Zeng et al, 2008;Kawase et al, 2011;Morgenstern et al, 2013;Young et al, 2013). For the ozone burden, Kawase et al (2011) also find increases under RCP4.5 and 8.5 in sensitivity tests that are similar to the CC4.5 and CC8.5 runs of this study.…”
Section: Ozone Burdensupporting
confidence: 55%
“…On the other hand, isolating the impacts of declining ODS concentrations, and the associated recovery of stratospheric ozone, on tropospheric composition has received attention in only a few studies (Kawase et al, 2011;Morgenstern et al, 2013;Zhang et al, 2014). Effects could occur through two main mechanisms: (i) increases in STE and (ii) increases in overhead ozone column with concomitant reductions in tropospheric photolysis rates.…”
mentioning
confidence: 99%
“…However, the version of the model used here does not have a comprehensive tropospheric chemistry scheme and therefore tropospheric ozone changes are not considered in this analysis. For a discussion on the impact of stratospheric ozone changes on STE in UM-UKCA see Morgenstern et al (2013) and Braesicke et al (2013).…”
Section: Ozonementioning
confidence: 99%
“…Stevenson et al, 2000;Prather et al, 2001;Revell et al, 2012a;Morgenstern et al, 2013;Naik et al, 2013;Voulgarakis et al, 2013). Generally, these studies have found that methane increases lead to ozone increases in most of the lower and middle atmosphere (below 1 hPa) which amplify the global warming associated with methane.…”
Section: Introductionmentioning
confidence: 99%
“…This means their chemical impacts occur mostly in the "chlorine layer" around 40 km and in the lower stratosphere over the poles (Brasseur et al, 1999). However, through dynamical feedbacks, transport, and impacts on ultraviolet and longwave radiation, such ozone depletion affects atmospheric composition throughout the troposphere and stratosphere (Madronich and Granier, 1992;Madronich, 1993;Fuglestvedt et al, 1994Fuglestvedt et al, , 1995Morgenstern et al, 2013). Southern Hemisphere climate change is thought to have been dominated in recent decades by ozone depletion (for a review see Thompson et al, 2011), but there is limited evidence for an effect of Arctic ozone depletion on the Northern Hemisphere circulation .…”
Section: Introductionmentioning
confidence: 99%